Comparison of platelet-to-lymphocyte and neutrophil-to-lymphocyte ratios with epithelial ovarian cancer stages - Tıraş, Halil İbrahim; Dülgeroğlu, Yakup; Aydın, Çetin (The European Research Journal, 2024)
Objectives: Epithelial ovarian cancer (EOC) is the most common histologic type among ovarian cancers. It is usually diagnosed at an advanced stage and the prognosis worsens. The aim of our study was to investigate the predictive value of serum platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR), which are systemic inflammatory response markers in EOC stages. Methods: In this study, 140 patients diagnosed with primary EOC in İzmir Katip Çelebi University Atatürk Training and Research Hospital Gynecology and Obstetrics Clinic between 01.01.2012-01.07.2019 were included. The cases were staged using the FIGO 2014 Ovarian Cancer Staging system. Whether the PLR and NLR values were different between the stages were analyzed with appropriate statistical analysis methods. Results: A total of 140 patients, 54 were in the early stage (Stage I: 47; Stage II: 7) and 86 were in the advanced stage (Stage III: 73; Stage IV: 13). The PLR and NLR values differed between the four stages (p = 0.003 and p = 0.032, respectively). The PLR value was different between the early and advanced stages (p = 0.033), the AUC value was 0.607, the optimum cut-off was 220, the sensitivity was 47%, and the specificity was 81% in the early and advanced stage discrimination. Accordingly, the Odds ratio of PLR for advanced EOC was 3.82 (95% CI: 1.70-8.57, p = 0.0011). Conclusions: The NLR and PLR values were found to have a prognostic value in the discrimination of EOC stages. It has been determined that PLR value may play a predictive role in advanced EOC before surgery.